Numerical Simulation and Experiment on Optical Packet Header Recognition Utilizing Reservoir Computing Based on Optoelectronic Feedback - Jie Qin; Qingchun Zhao; Hongxi Yin; Yu Jin; Chang Liu (IEEE Photonics Journal)
An optoelectronic feedback reservoir computing (RC) system that can identify optical packet headers for an optical packet switching (OPS) network is proposed and implemented by the numerical simulation and the experiment in this paper. First, a simulation system of optical packet header recognition based on the optoelectronic feedback RC is established through optimizing its parameters. It is shown that the optoelectronic feedback RC system can correctly identify optical packet headers with lengths from 3 bits to 32 bits and that the recognition word-error rate (WER) is 0. Then, an experiment system consistent with the optimal simulation system is set up, whose WER for the 3-bit header recognition is only 1.25%. The experimental results also indicate that the bias voltage of the Mach–Zehnder modulator (MZM) has a significant impact on recognition results. When the RC system is in the critical state between the multiple-period oscillation and the chaos, the maximal Lyapunov exponent is slightly larger than 0, and the recognition normalized root-mean-square error (NRMSE) reaches its minimal value.